Head Start Funding Expansions and Program Inputs - Chris M. Herbst; Esra Kose (Institute of Labor Economics (IZA), 2021)
Our paper provides some of the first evidence on the effect of the Head Start funding expansions on program inputs. We take advantage of the county-year variation in funding increases that were implemented due to a number of legislated policy changes in the late 1980s and throughout the 1990s. By focusing on the period between 1988 and 2007, we show that the funding increases were directed at increasing program enrollment and full-time enrollment. We also show that the funding expansions were used to make a number of quality-related in- vestments, including increasing the number of teachers and staff, and upgrading the skill-level of teachers.
Keywords: H52; I28; 330; national government expenditures and education; head start; early childhood education